PENGARUH BRAND IMAGE, ELECTRONIC WORD OF MOUTH, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENGINAP DI HOTEL 88 MANGGA BESAR 120 - Dafa Kamil Azizi; Surono (Human Capital Development, 2025)
This study aims to analyze the effect of Brand Image, electronic word of mouth (E-WOM), and service quality on consumer stay decisions at Hotel 88 Mangga Besar 120. A quantitative method with accidental sampling was applied to 150 respondents, and the data were analyzed using multiple linear regression. The results show that all three variables have a positive and significant influence on stay decisions, both partially and simultaneously, with Brand Image emerging as the most dominant factor. The model explains 48.3% of the variation in consumer decisions. These findings suggest that hotel managers should strengthen brand communication, manage online reviews effectively, and maintain service quality consistently to enhance consumer decision-making and increase occupancy rates.